3(2x-2)=4(x+4)

Simple and best practice solution for 3(2x-2)=4(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-2)=4(x+4) equation:


Simplifying
3(2x + -2) = 4(x + 4)

Reorder the terms:
3(-2 + 2x) = 4(x + 4)
(-2 * 3 + 2x * 3) = 4(x + 4)
(-6 + 6x) = 4(x + 4)

Reorder the terms:
-6 + 6x = 4(4 + x)
-6 + 6x = (4 * 4 + x * 4)
-6 + 6x = (16 + 4x)

Solving
-6 + 6x = 16 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-6 + 6x + -4x = 16 + 4x + -4x

Combine like terms: 6x + -4x = 2x
-6 + 2x = 16 + 4x + -4x

Combine like terms: 4x + -4x = 0
-6 + 2x = 16 + 0
-6 + 2x = 16

Add '6' to each side of the equation.
-6 + 6 + 2x = 16 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = 16 + 6
2x = 16 + 6

Combine like terms: 16 + 6 = 22
2x = 22

Divide each side by '2'.
x = 11

Simplifying
x = 11

See similar equations:

| 8x+10-2x+36=4x+15+8x-28 | | n+1=13-2n+n | | 10y-4-8=20 | | 3(3.99)+1b-0.11=5b | | (2x-3)(2x+3)=55 | | x^2-21x+75=0 | | 5y-4=8+y | | 3x-2=7x+6 | | -4+4/5x=6 | | -5=9+c-4 | | 5x-3+4x-24=3x+2+4x-9 | | -2(6+4b)=-6b | | 10y-4g-8=20 | | r/10+1.1=0.3 | | 2n+3.5=6.7 | | W^2+7=w^3+9 | | (A^-3b6-4/a^7b^3)(a^3b^4/a^-3b^-3)^2 | | 5x-3(x-5)=15 | | 2p-2=14+6p | | 6(r+7)=35+5r | | 3x=56+7(9)y | | 4t+8t=60 | | 9m+108=9m*5 | | 3k-5=2(k+1) | | 1/2(8x-5/11)-10/11(5x+3/8)=1/4(2x+5) | | X/3-8=-15 | | d/-4+3f=14 | | 5t+8t=60 | | 12=-4-11 | | -66=4+10x | | 3x+12=2x+8 | | m+12=5 |

Equations solver categories